(untitled) (Balneo and PRM Research Journal, 2024)
Attention deficit and hyperactivity disorder (ADHD) is seen as a long-lasting and chal-lenging condition that affects various areas of life, such as academic and career success, relationships, and daily activities. Both the mind and the muscles jump from one task to another, failing to complete the activity, and thus difficulties arise in carrying out activities such as writing, tying shoelaces, riding a bicycle and more. Banal activities we would say, but essential for a normal lifestyle. Medical recovery has a signifiant contribution in relieving symptoms and treating many pathologies, in both physical and mental relaxation. Moreover, it has been shown countless times that physical activity reduces stress, mainly based on muscle relaxation and improving cognitive and motor function through the development of neural functions. More and more children are diagnosed with this disorder, but, not enough attention is paid to these cases, which is one of the reasons why we chose to address this topic. The paper aims to analyze studies carried out in recent years in different countries on motor impairments and other complications that can present children with ADHD, but also the way that balneophysiokinetotherapy has a positive effect in their therapy, being an essential form of therapy, alongside the psychological or medicinal one. The studies analyzed confirm the benefits of physical exercise for children diagnosed with ADHD, showing visible effects on both the motor skills of the children and their lev-els of agitation and attention deficit. Although movement therapy is widely used in this condition, there are no protocols standardizing the type, duration, and intensity of exer-cise programs used. Occupational therapy, massage, and yoga have been noted for their beneficial effects on patients diagnosed with ADHD.